(3cJGH YeOI GdCWHGA aj eYQaI GdOGA hGdOhGAs ((3eMeO Hf eMeO Hf CHj WGdH Hf eMeO Hf GdMSf GdWHjH s)
(3ChdgG (B:s
(3GdMeO HdG ZGjI hGdTcQ HdG fgGjI def hLhOg hGLH dPGJg CeG HYO adG jNai Ydi BQGA Phi GdCagGe Cf TQa GdYde HTQa ehVhYI s
(3BNQgG (B:s
(3ajchf GdeQcH HGQOkG ai GdNeS hKdGK NeS ef GdOQLI GdChdi aHgPG GdWQjb jSJNQL WHGFY GdeQcHGJ hGddg CYde HGdUhGH s
(3HBNQg fbhds
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdWHs